Peer Tutor Method as a Solution to Improve the English Language Skills of UIN Walisongo Semarang Students - Fat Maulana, Fat; Najichah, Amalia; Fitroh, Nailatul; Khumaira, Anindya Nazmi (PT Ilmu Inovasi Nusantara, 2024)
In the current era, numerous learning methods can be employed to enhance the effectiveness of learning. One such method is the peer tutor method, which has been widely utilized in language learning. This research focuses on the application of the peer tutor method as a solution for improving English language skills. The subjects of the study are students of UIN Walisongo who are members of the Walisongo English Club (WEC). The Student Activity Unit (UKM) Walisongo English Club (WEC) conducted this research to ascertain the impact of peer tutoring on the English language proficiency of Walisongo State Islamic University of Semarang students. This study employed a qualitative approach and utilized data collection techniques, including questionnaires, interviews, and documentation. The results demonstrated that the implementation of the peer tutor method yielded numerous benefits for the WEC members, including enhanced English language proficiency, a more relaxed learning environment, and elevated self-assurance. Additionally, the method facilitated increased confidence in English communication. However, there were limitations due to the limited knowledge of the peer tutors. Nevertheless, it can be concluded that the peer tutor method is an effective solution for improving the English language skills of UIN Walisongo Semarang students.